This can't be answer it depends on wha the equation is
100 percent because 45 % is always in between 30 and 50 %
The is answer is 324. The previous number is multiplied by -3.
Answer:
(-4x - 2)(-5x) + (-4x - 2)(3)
Step-by-step explanation:
Your polynomial is
(-4x - 2)(-5x + 3)
The distributive property states that
a(b + c) = ab + ac
Let a = -4x - 2. Then
(-4x - 2)(-5x + 3) = a(5x + 3) = a(-5x) + a(3)
Substitute the value of a.
a(-5x) + a(3) = (-4x - 2)(-5x) + (-4x - 2)(3)
You have just distributed the first binomial (-4x - 2) among the terms of the second binomial.
1:3 can be another ratio of black fish to white fish